Pemetaan deferred tax expense dan deferred tax liability dengan real earnings management: studi bibliometrik dan literatur review melalui vosviewer - Jibril, Hosianda (Maliki Interdisciplinary Journal, 2025)
This study analyzes the influence of Deferred Tax Expenses and Deferred Tax Liabilities on Real Earnings Management (REM) by employing a bibliometric approach using VOSviewer and a literature review. The research data were obtained from 500 articles retrieved from the Publish or Perish database, using relevant keywords over the period from 2015 to 2025. These articles were analyzed descriptively and visualized with VOSviewer to map the development of research on deferred tax and real earnings management topics. The analysis results indicate that research related to Deferred Tax is divided into several clusters, with the main themes focusing on the impact of Deferred Tax Expenses and Deferred Tax Liabilities on real earnings management. These findings can serve as a valuable reference for researchers and policymakers in understanding the effects of deferred tax on earnings management in companies